UJI SITOTOKSIK DAN AKTIVITAS ANTIBAKTERI EKSTRAK DAUN PANDAN LAUT (Pandanus Odorifer) TERHADAP BAKTERI Staphylococcus aureus - Shinta Puspasari; Nurhamidah Nurhamidah; Hermansyah Amir (ALOTROP, 2020)
This study aims to determine the activity of marine pandanus extract(Pandanus odorifer) as cytotoxic and antibacterial to Staphylococcus aureus bacteria. This research begins with phytochemical test conducted to find out the secondary metabolite compounds contained in the leaves of P. odorifer. Cytotoxic testing was performed using BSLT method. An antibacterial test was performed against the activity in inhibiting the growth of S. aureus bacteria using a modified disc diffusion method. The results of phytochemical tests showed that ethanol extract of pandanus leaves contain saponin, flavonoids, tannin and terpenoid compounds. The results of cytotoxic test of sea pandan have a very strong toxic level with LC50 value of 4.3557 ppm.The result of measurement of the highest inhibiting zone diameter was obtained at the concentration of 5x104 ppm is 6 mm with the power of inhibitory that is medium. Based on the results of this study can be concluded that the leaves of sea pandan are cytotoxic and have activity as antibacterial